Neutron activation analysis for cement elements using an IECF device as a high energy neutron source. Issue 11 (2nd March 2016) - Zadeh, E. Eftekhari; Sadighzadeh, A.; Salehizadeh, A.; Nazemi, E.; Roshani, G. H.
Abstract : In this study, Neutron Activation Analysis (NAA) for cement elements using an Inertial Electrostatic Confinement Fusion (IECF) facility as a high energy neutron source is investigated. Abstract : Neutron Activation Analysis (NAA) is an important technique for quantitative and qualitative multi-element analysis. The Inertial Electrostatic Confinement Fusion (IECF) device is known as a fast and monoenergetic neutron generator. In this study, NAA for cement elements using an IECF facility as a high energy neutron source was investigated. The Iranian IECF device was simulated using the MCNPX code version 2.7 and the 'ACT card' was used to consider the induced delayed gamma-ray spectra during delayed gamma NAA (DGNAA). The peaks related to Al, Ca, Fe and Si were distinguished precisely, which shows the applicability of IECF as an appropriate neutron source for DGNAA analysis for cement elements.